Primary care access and foregone care: a survey of transgender adolescents and young adults. (21st November 2017) - Clark, Beth A; Veale, Jaimie F; Greyson, Devon; Saewyc, Elizabeth
Abstract: Objective: To examine the issues of primary care access and foregone health care among transgender adolescents and young adults. Methods: This cross-sectional analysis of data from the Canadian Trans Youth Health Survey was conducted online during 2013–2014. Participants included 923 youth aged 14–25 (323 adolescents aged 14–18 and 600 young adults aged 19–25). Main outcome measures were self-reported general and mental health status, comfort discussing transgender identity and health care needs with general practitioners, and types of and reasons for self-identified foregone health care. Results: Most youth reported poor/fair general and mental health status. Comfort with a family doctor was positively correlated with both general health ( r (528) = 21, P < 0.001) and mental health ( r (450) = 26, P < 0.001) status, as was having a doctor who was aware of one's transgender status. 47.2% ( n = 219) of young adults reported foregoing needed health care. Among adolescents, levels of comfort with family doctor were negatively correlated with foregone mental health care in the previous 12 months ( F 3, 166 = 3.829, P = 0.011), but not correlated with foregone physical health care ( F 3, 165 = 0.506, P = 0.679). Reasons for missing needed care spanned the dimensions of health care access, ranging from cost barriers to previous negative experiences with health care providers, and concerns that a doctor would be uneducated about transgender people. Conclusion: General practitioners can play a key role in improving the health of transgender youth by demonstrating understanding of the health care needs of transgender youth and competence in gender-affirming care, and by ensuring that their practices are accessible to all transgender youth in need of care.